2018
DOI: 10.1111/nph.15152
|View full text |Cite
|
Sign up to set email alerts
|

The impact of domestication and crop improvement on arbuscular mycorrhizal symbiosis in cereals: insights from genetics and genomics

Abstract: Contents Summary 1135 I. Introduction 1135 II. Recruitment of plant metabolites and hormones as signals in AM symbiosis 1136 III. Phytohormones are regulators of AM symbiosis and targets of plant breeding 1137 IV. Variation in host response to AM symbiosis 1137 V. Outlook 1137 Acknowledgements 1139 References 1139 SUMMARY: Cereals (rice, maize, wheat, sorghum and the millets) provide over 50% of the world's caloric intake, a value that rises to > 80% in developing countries. Since domestication, cereals have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 40 publications
0
47
0
Order By: Relevance
“…Modern breeding efforts have focused on maximizing yield under homogeneous environments with large quantities of synthetic inputs. It is not clear how the breeding process has impacted the balance of AM symbiosis (discussed in Sawers et al, 2008Sawers et al, , 2018, but major crops do retain the capacity to interact with AMF and they conserve the necessary molecular machinery (e.g. Gutjahr et al, 2008;Nadal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Modern breeding efforts have focused on maximizing yield under homogeneous environments with large quantities of synthetic inputs. It is not clear how the breeding process has impacted the balance of AM symbiosis (discussed in Sawers et al, 2008Sawers et al, , 2018, but major crops do retain the capacity to interact with AMF and they conserve the necessary molecular machinery (e.g. Gutjahr et al, 2008;Nadal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…1322–1336) examine plant metabolic plasticity in stressed tomato plants, and note that AM symbioses can help plants deal with this stress, and the Tansley insight by Sawers et al . (; in this issue of New Phytologist , pp. 1135–1140) examines AM symbiosis in light of domestication and crop improvement in cereals.…”
Section: Mycorrhizal Fungal Community Ecologymentioning
confidence: 98%
“…Furthermore, a few studies have reported that both artificial management of plant growth environment and conditions, and plant domestication affect the community structure of rhizosphere and endosphere microbiomes [27,119,146,147]. Wild plant species preserve more diversity in associated microbiota for their survival against stress resistance than the domesticated crops.…”
Section: Influences Of the Community Compositions Of Rhizosphere Phymentioning
confidence: 99%